2023
DOI: 10.1111/jocd.15676
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters in patients with acnes

Abstract: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous units which mainly localized on the face, chest, and back. 1 It is the eight most common skin disease and the most common skin condition in adolescents, affecting approximately 85% of teenagers. 2 Numerous people all around the world were also plagued by acne scar and other complications. The pathogenesis of acne vulgaris

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Studies examining the NLR in AV also appear in the literature. One such study determined no significant relationship was found between NLR and severity of AV [ 11 ]. In contrast, another study reported higher NLR values in patients with AV than in a control group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the NLR in AV also appear in the literature. One such study determined no significant relationship was found between NLR and severity of AV [ 11 ]. In contrast, another study reported higher NLR values in patients with AV than in a control group [ 12 ].…”
Section: Discussionmentioning
confidence: 99%